Handbook: Rural extension, Volume 1: Basic issues and concepts - Hoffmann, Volker; Gerster-Bentaya, Maria; Christinck, Anja; Lemma, Mamusha (CTA / GTZ / Margraf / Universität Hohenheim, 2009)
This is the first book in a three-volume series on rural extension (see 1553) aimed at promoting greater transparency in extension planning, implementation and evaluation. It discusses the role of extension in rural development, extension approaches, concepts and methods, and the use of extension aids and media. The book includes case-studies illustrating approaches and methods, and concludes with practical guidelines and checklists.